Developing Cluster for Mountains and Hills Tourism in Ekiti State, Southwest, Nigeria - P.A, Agbebi; A.A, Ogunjinmi; O.O, Oyeleke; B.O, Adetola (Journal of Tourism Management Research, 2021)
The study described the development of cluster for mountains and hills tourism potentials in Ekiti State. Mapping and direct observation were used to collect both primary and secondary data. Mapping was done by the use of Geographic Information Sysytem (GIS), and Remote Sensing Tools (RST) which properly identified the GPS corodinates and photographs of mountains and hills locations in Ekiti State. These were later downloaded using Arc GIS software for further analysis and the production of multiple maps such as elevation, slope map, shaded relief map and contour map of Ekiti State. Findings clealy showed 57 elevations which were 600m and above, and 245 elevations that were less than 600m in different proportions and heights spread across 27 communities in the 3 zones of Ekiti State. Thus, communities that have two or more mountains and hills at different locations formed cluster as tourism destinations with proposed headquaters where all administrative works will be controlled. The study will ensure that the selected communities in Ekiti State would be given priority in massive infrastructural development to enable potential visitors and tourists to mountains and hills in Ekiti state have deserving comforts that could be compared to other existing mountains and hills destinations outside Nigeria. Conclusively, the government of Ekiti should provide adequate funds for infrastructure in all communities where mountains and hills are domociled.